2021
DOI: 10.3389/ffgc.2021.668895
|View full text |Cite
|
Sign up to set email alerts
|

A Parasite’s Paradise: Biotrophic Species Prevail Oomycete Community Composition in Tree Canopies

Abstract: Oomycetes (Stramenopiles, protists) are among the most severe plant pathogens, comprising species with a high economic and ecologic impact on forest ecosystems. Their diversity and community structures are well studied in terrestrial habitats, but tree canopies as huge and diverse habitats have been widely neglected. A recent study highlighted distinct oomycete communities in the canopy stratum compared to the ground region of three temperate deciduous trees (Quercus robur, Tilia cordata, Fraxinus excelsior). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…For host trees, their epiphytes and epifauna, microbiota can engage in various relationships of interest, including mutualism (Mejía et al, 2014), saprotrophism (Song et al, 2017), and pathogenism (Laine et al, 2014), though many, of course, have no known relationship. Parasitic and pathogenic signals in stemflow samples may be useful to assess the extent and severity of microbial disease agents, from viruses (D'Amico and Elkinton, 1995) and bacteria (Griffin and Carson, 2015), to protists, especially a group of particularly effective plant pathogens, oomycetes (Jauss et al, 2021). Viruses can travel in the waters draining through canopies, originating from literal reservoirs of water, like dendrotelmata (Kollars et al, 2019;Diouf et al, 2020), and from cadaverous reservoirs, like putrefying gypsy moths (D'Amico and Elkinton, 1995).…”
Section: Canopy Microbial Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For host trees, their epiphytes and epifauna, microbiota can engage in various relationships of interest, including mutualism (Mejía et al, 2014), saprotrophism (Song et al, 2017), and pathogenism (Laine et al, 2014), though many, of course, have no known relationship. Parasitic and pathogenic signals in stemflow samples may be useful to assess the extent and severity of microbial disease agents, from viruses (D'Amico and Elkinton, 1995) and bacteria (Griffin and Carson, 2015), to protists, especially a group of particularly effective plant pathogens, oomycetes (Jauss et al, 2021). Viruses can travel in the waters draining through canopies, originating from literal reservoirs of water, like dendrotelmata (Kollars et al, 2019;Diouf et al, 2020), and from cadaverous reservoirs, like putrefying gypsy moths (D'Amico and Elkinton, 1995).…”
Section: Canopy Microbial Communitiesmentioning
confidence: 99%
“…These studies report that fungal conidia can be abundant in stemflow: up to billions of conidia ha −1 y −1 (Magyar et al, 2021). It has been recently observed that tree canopies can hold more species of parasitic oomycetes with lifestyles that exclusively feed on living host tissue than in other forest compartments, implying tree canopies may themselves be a major reservoir for parasitic protists (Jauss et al, 2021). As stemflow washes much of the canopy, it may provide an integrated signal of this parasitic protist community and its compositional or functional dynamics.…”
Section: Canopy Microbial Communitiesmentioning
confidence: 99%